Links between marine biotic evolution and carbonate platform and petroleum reservoir development in the Guajira Basing, Colombia Caribbean ; Final technical and financial report (2016)
This document shows the final activities and results obtained in the last year on the proyect. The focus of the project was to characterize the composition, morphology and distribution of the fossil assemblages, as well as to interpret the paleoecology of the fossil reefs at the Siamaná Fm. in La Guajira Basin. In order to achieve this goal we have developed an integrated program of collection, analysis, and synthesis of the disparate range of information on the geological record of environmental and biotic change in fossil coral reefs ecosystems of La Guajira Basin. This synthesis incorporated information on carbonate basin that will be useful for reservoir predictions bringing relevant information to the petroleum industry. This study is the first to correlate the stratigraphic sequence in the area and compare the changes in the carbonate development through the Oligocene / Miocene transition, evaluating the faunal tumover in reef and platform faunas. We evaluated the composition, lateral and vertical distribution of the various components of the reefal assemblage (e.g corals, foraminifers) in order to understand the stratigraphic evolution of the reefal deposits of the Siamaná Formation. The carbonate rocks in this area are not only important hydrocarbon reservoirs, but their onset, termination and major internal unconformities are tied to the large scale stratigraphic development of the region. A modern review of carbonate facies and unconformities can impact hydrocarbon exploration for both assessing reservoir risks, as well as for predicting stratigraphic sequences over the entire Caribbean Sea. Besides, the study of carbon dioxide environments for global climatic and eustatic variations may provide models for predicting future peculiarities in ecosystem reactions depending on the regional location and recent history